2019
DOI: 10.2196/12521
|View full text |Cite|
|
Sign up to set email alerts
|

What Do Patients Say About Doctors Online? A Systematic Review of Studies on Patient Online Reviews

Abstract: Background The number of patient online reviews (PORs) has grown significantly, and PORs have played an increasingly important role in patients’ choice of health care providers. Objective The objective of our study was to systematically review studies on PORs, summarize the major findings and study characteristics, identify literature gaps, and make recommendations for future research. Methods A major database search was completed in January … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
100
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(117 citation statements)
references
References 92 publications
6
100
1
5
Order By: Relevance
“…Our data also showed that higher overall ratings were associated with shorter wait times ( g =0.26). This finding has been reported and discussed in several studies of online patient reviews [ 1 ]. Patient review websites such as HealthGrades and RateMDs have included “wait time/punctuality” as a default measure for healthcare providers.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Our data also showed that higher overall ratings were associated with shorter wait times ( g =0.26). This finding has been reported and discussed in several studies of online patient reviews [ 1 ]. Patient review websites such as HealthGrades and RateMDs have included “wait time/punctuality” as a default measure for healthcare providers.…”
Section: Discussionsupporting
confidence: 82%
“…Over the last few years, researchers have begun a systematic analysis of online patient reviews. In the United States, several empirical studies investigating online reviews of general healthcare services and specialties are well documented, but such studies have not been performed in dentistry [ 1 ]. To the best of our knowledge, this study represents the first study of online reviews of dental care in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations